Application of the Stevenson-Porter Fuzzy Time Series Method in Forecasting Oil and Gas Import Values - Hairatun Hisanun; Aswi Aswi; Muhammad Fahmuddin S (Jurnal Varian, 2026)
The value of Indonesia’s oil and gas imports is one of the important indicators of Indonesia’s economic growth. The high value of imports over time shows that Indonesia has not been able to manage domestic energy supply properly, which can threaten national energy security. Therefore, an accurate forecasting method is needed to forecast the value of Indonesia’s oil and gas imports. The objective of this research is to forecast the value of Indonesia’s oil and gas imports for January 2025. The method used in this study is the Stevenson–Porter fuzzy time series method, using monthly data on Indonesia’s oil and gas import values from January 2010 to December 2024. The results indicate that the forecasted value of Indonesia’s oil and gas imports for January 2025 is US$ 2,553.5 million, with a Mean Absolute Percentage Error (MAPE) of 6.21%, indicating very good forecasting accuracy. The forecast result can support policymakers in improving energy import planning and strengthening Indonesia’s national energy security.